Sophist dan Pengaruhnya Terhadap Pemikiran Islam Liberal di Indonesia - Hasib Amrullah (Tasfiyah: Jurnal Pemikiran Islam, 2017)
The name Sophist, is rarely found in contemporary scientific discussion. But the model of thinking still exists in some scientific studies. This principle seemed to be a current which can not be avoided. In fact, because of the swift, this current propagates in the primary Islamic studies. It can be encountered in some of the growing discourse in the discourse of Islam’s in Indonesia. Essential nature of thought such sophist; opine not to seek the truth, relativism, agnosticism and skepticism converge in the paradigm of liberal thinkers in Indonesia. The principle of al-Lā adriyyah, al-’Indiyyah, and al-’Inādiyyah are still exist and grow without using the identity of sophist. Consequently, the argument collision impact on social clash of Islam and of itself the product of liberal thought into popular discourse. The absence of theological principles on Science discipline, anti-authority stance on the ‘Ulama’, plus the loss of judgment of right “Ḥaqq” and wrong “Bhaṭil” in the argument, show the influence of sophist into Islamic intellectual thinkers. This shows that the problem of thought may impact onto problematic attitude.